Comparative private law: online defamation and service provider liability- a comparative study - Bezzenberger, Julia (Centre for Law and Society, 2026)
"The Internet is a unique and wholly new medium of world-wide human communication." 1 It enables people to communicate with one another with unprecedented speed and efficiency and is rapidly revolutionising how people share and receive information. From the time when the first vacuum tube computers were introduced in the 1950s it took the U.S. Department of Defence only until 1969 to create the Internet. At that time their goal was to create a decentralised system to protect data and communication in the advent of a thermonuclear war. But they had started a development that could not be stopped anymore. Overtime, the Internet evolved as a world-wide network of government, academic and commercial computer systems and databases linking academics, scientists and government officials. 2 Despite this dramatic growth, it was only in this decade that individuals outside of these spheres used the Internet. Today computers and modems are irreplaceable items of everyday life and the Internet has grown faster than anyone, even its greatest proponents, could have imagined. It is not only the preferred mode of communication for millions of people, but also a source of vast information. Individual users send messages across cyberspace, browse online magazines and newsletters, and participate in "chat rooms", discussing topics with others who share similar interests. One can buy plane tickets, take classes, order nearly eve1ything or publish whatever one wants to let the world know.